Effect of Ge Nanoparticles in the Core of Photonic Crystal Fiber on Supercontinuum Generation. (16th May 2019) - Ju, Seongmin; Lee, Yuseung; Jeong, Seongmook; Kim, Youngwoong; Kim, In-Sik; Ko, Do-Kyeong; Han, Won-Taek
Abstract : The effect of Ge nanoparticle (Ge NP) incorporation in the germanosilicate glass core of the photonic crystal fiber (PCF) on supercontinuum generation (SCG) was investigated. The Ge NP-doped germanosilicate glass core PCF was fabricated by using the modified chemical vapor deposition (MCVD) and the stack-and-draw processes. The average diameter of Ge NPs embedded in the core of the PCF was 4.2 nm. The absorption peaks at 480 nm and 515 nm and the band from 600 to 800 nm were attributed to the Ge NPs in the core of the PCF. SCG of the 490 nm bandwidth (598 nm 1088 nm) with a conversion efficiency of 31% was obtained by pumping at 800 nm with the Ti:sapphire femtosecond laser of 160 mW with 35 fs pulse at 1 kHz repetition rate, resulting from the enhanced optical nonlinearity from Ge NPs as well as the PCF structure of the fiber.